2014
DOI: 10.1093/jmcb/mju050
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C-δ and -β coordinate flow-induced directionality and deformation of migratory human blood T-lymphocytes

Abstract: T-lymphocyte migration under flow is critical for immune responses, but the mechanisms by which flow modulates the migratory behaviors of T-lymphocytes remain unclear. Human peripheral blood T-lymphocytes (PBTLs), when stimulated with phorbol 12-myristate 13-acetate (PMA), stretched their cell bodies dramatically and moved along the flow direction. In contrast, stromal cell-derived factor-1α-stimulated PBTLs deformed and migrated in a random manner. Here we elucidated the molecular mechanisms underlying flow-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Additionally a study of Grybko et al showed that PRKCA translocates in synergy with PRKCQ to the IS of cytotoxic T-cells to mediate lytic granule exocytosis [63]. PRKCB coordinates together with PRKCD the responsiveness of migratory human blood T-lymphocytes [64]. Various PKC knockout studies analyzing PRKCA -, PRKCB -, PRKCE -, PRKCH - or PRKCQ -deficient mice observed defects in immune cell activation and function [6569].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally a study of Grybko et al showed that PRKCA translocates in synergy with PRKCQ to the IS of cytotoxic T-cells to mediate lytic granule exocytosis [63]. PRKCB coordinates together with PRKCD the responsiveness of migratory human blood T-lymphocytes [64]. Various PKC knockout studies analyzing PRKCA -, PRKCB -, PRKCE -, PRKCH - or PRKCQ -deficient mice observed defects in immune cell activation and function [6569].…”
Section: Discussionmentioning
confidence: 99%
“…These initial contacts occur via actin-rich protrusions at the leading edge of migrating T cells, which are regulated by protein kinase Cδ (PKCδ), RAC1 and downstream effectors of actin polymerization including Wiskott Aldrich syndrome protein (WASP) 28 . These protrusions form the first point of contact between cells as synapses form, and they may correspond to the actin foci that have been reported to be required for the activation of PLCγ1, via WASP 29 .…”
Section: Actin Flowmentioning
confidence: 99%
“…Illustration on the underlying algorithm to detect miRNA k-mer enrichments in possible target sequences. Human mature miRNA 5p/3p sequences were collected from miRBase v21, while 3 0 UTRs for human were acquired from Ensembl Release 91 [51]. After extracting and mapping the k-mers with up to 2 mismatches for each possible binding site, the best k-mer was selected.…”
Section: Plasmidsmentioning
confidence: 99%
“…Recently, we identified miR-34a as most up-regulated miRNA in CD3+ T cells of lung cancer patients targeting five protein kinase C family members including PRKCA, PRKCB, PRKCE, PRKCH and PRKCQ [31]. Besides the central role of these PKC isozymes in carcinogenesis, these miR-34a target genes are involved in cell signaling through the immunological synapse (IS) of T cells downstream of the T cell receptor (TCR) [47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%